Perancangan Interior Fasilitas Tunggu Transportasi Umum di Surabaya - Lo Wilson Lesmana; mariana wibowo (Intra, 2015)
This public transportation waiting facility is designed in order to accommodate Surabaya city’s need of functional public transportation anticipation place, provided for any kind of citizens. The main facilities featured in this design are the shelter from weather, comfortable yet unabusable seats, supports for the disabled, and interesting decorative arts. The concept used in this design is “Livability”, referring to a good environment for a community to live in. There are certain principles emphasized to achieve that concept, such as “comfortable”, “vibrant”, “safe”, “enduring”, and “excellence”. The result established by this design is a comfortable, interesting, and safe environment so people can interact well with each other while waiting for the public transportation.